2015
DOI: 10.1071/fp15135
|View full text |Cite
|
Sign up to set email alerts
|

Response of leaf water status, stomatal characteristics, photosynthesis and yield in black gram and green gram genotypes to soil water deficit

Abstract: Drought is one of the most important abiotic stresses constraining crop productivity worldwide. The objective of the present study was to investigate the differences in drought tolerance at leaf and stomatal level of black gram (genotypes: T9, KU 301, PU 19, USJD 113) and green gram (genotypes: Pratap, SG 21–5, SGC 16, TMB 37). Drought was applied for fifteen consecutive days at flowering stage (35 days after sowing). Mid-day leaf water potential (ΨL), leaf area, photosynthesis rate (PN), leaf chlorophyll, sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
9
7
0
Order By: Relevance
“…Decreased leaf water potential (w) under stress may be due to loss of gradient (w) between the soil and roots, which is the guiding principle for water movement and decline in transpiration pull (Table 1). Our results are in line with the findings of Baroowa et al (2015) who reported similar trends of water potential in mungbean under water deficit. Among the rhizobial treatments, mean maximum leaf water potential was observed in MR 63 (-0.78 MPa) followed by MB 17a (-0.82 MPa) and it was minimum in RDF .…”
Section: Methodssupporting
confidence: 93%
“…Decreased leaf water potential (w) under stress may be due to loss of gradient (w) between the soil and roots, which is the guiding principle for water movement and decline in transpiration pull (Table 1). Our results are in line with the findings of Baroowa et al (2015) who reported similar trends of water potential in mungbean under water deficit. Among the rhizobial treatments, mean maximum leaf water potential was observed in MR 63 (-0.78 MPa) followed by MB 17a (-0.82 MPa) and it was minimum in RDF .…”
Section: Methodssupporting
confidence: 93%
“…Stomatal limitations reduced the gaseous exchange between leaf and atmosphere which is the main cause for reduced A, E and gs. These corroborates with earlier reports in legume crops such as Fababean [79], chickpea [77], common bean [80,81] and mungbean [22,82] under drought stress. The physiological mechanism has been explained in other studies which states that stomatal closure mediated by ABA during drought stress is the primary limitation of photosynthesis [83,84].…”
Section: Combined Stress Influences Water Relation Pigment Concentrasupporting
confidence: 93%
“…In the present study, total chlorophyll was significantly reduced under drought stress in comparison to control in sensitive accessions (IC73401 and IC280489). Several reports mentioned a reduction in chlorophyll in several crops exposed to drought stress such as in common bean [20], cluster bean [21], soybean [76], chickpea [77] and mungbean [22]. Although increased chlorophyll concentration is a typical trait under low P stress but we did not find significant change which corroborates with results in common bean [78].…”
Section: Combined Stress Influences Water Relation Pigment Concentrasupporting
confidence: 89%
See 1 more Smart Citation
“…One interesting trend observed in both formative stages was that significantly higher Gs during water deficit conditions appear to have better agronomic characteristics and lower EC values, as well as higher AOA. It is already known how significant stomatal conductance is during drought conditions [55]. Reduced photosynthetic rate, as well as stomatal conductance during drought, resulted in low levels of internal CO 2 concentration due to inhibition of photosynthetic enzymes such as Rubisco [45,56].…”
Section: Discussionmentioning
confidence: 99%